Prevalence of multidrug resistant uropathogens isolated from different age groups in South-India: a cross-sectional study - K. S., Harish Kumar; A., Asina P.; Theckel, Philip G.; Divakaran, Binoo; Sathar, Sajmi; R., Asalatha; S., Remya V. (International Journal of Research in Medical Sciences, 2022)
Background: Urinary tract infections (UTIs) continue to be one of the most common infections encountered by clinicians. The purpose of this study is to identify relevant multidrug resistance (MDR) patterns in South India. Methods: 401 urine culture samples with significant bacteriuria were collected from labs in South India between January 2019 and December 2020. Routine biochemical tests were conducted for primary identification of uropathogens. Antibiotic susceptibility testing was performed according to Clinical and Laboratory Standards Institute (CLSI) guidelines. Statistical package for the social sciences (SPSS) 16 and Microsoft excel were used to analyse data and determine MDR patterns. Results: The results showed that 54% of cultures with significant bacteriuria exhibited an organism with multidrug resistance. Of these, extended-spectrum beta-lactamases (ESBL) resistance was confirmed in 34.9%. Furthermore, over half (54%) of significant cultures were from outpatients. The incidence of UTIs was highest during the summer and at the lowest in the second phase of the monsoon season. Conclusions: Although the sample collection was limited to a few centres in South India, the results of our study justifies the rationale behind stringent regulation of antibiotic use and careful monitoring of antimicrobial resistance.